Domestic negotiations : gender, nation, and self-fashioning in US Mexicana and Chicana literature and art - McMahon, Marci R., 1975- (New Brunswick, N.J. : Rutgers University Press, 2013)
This book explores how U.S. Mexicana and Chicana authors and artists across different historical periods and regions, and how they use domestic space to actively claim their own histories. Drawing from a range of archival sources and cultural productions, the book demonstrates how the very sites of domesticity are used to engage with the many political and recurring debates about race, gender, and immigration affecting the lives of Mexicanas and Chicanas from the early twentieth century up through the twenty-first century.
Domestic Power. The Chili Queens of San Antonio : Challenging Domestication through Street Vending and Fashion ; Claiming Domestic Space in the US-Mexico Borderlands : Jovita González and Eve Raleigh’s Caballero and Cleofas Jaramillo’s Romance of a Little Village Girl ; Domestic Power across Borders: Fabiola Cabeza de Baca’s Home Economics Work in New Mexico and Mexico -- Domesticana. Postnationalist and Domesticana Strategies : Sandra Cisneros’s The House on Mango Street and Carmen Lomas Garza’s Familias ; Patssi Valdez’s “A Room of One’s Own” : Self-Fashioning, Glamour, and Domesticity in the Museum and Hollywood ; Redirecting Chicana/Latina Representation : Diane Rodríguez’s Performance and Staging of the Domestic -- Epilogue : Denaturalizing the Domestic.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: American literature -- Mexican American authors -- History and criticism; American literature -- Women authors -- History and criticism; Identity (Psychology) in literature; Mexican Americans in literature; Mexican American women in literature; Mexican American arts; Mexican American women artists; Nationalism and literature -- United States -- History; Littérature américaine -- Auteurs américains d'origine mexicaine -- Histoire et critique; Écrits de femmes américains -- Histoire et critique; Identité (Psychologie) dans la littérature.; Américains d'origine mexicaine dans la littérature.; Arts américains (mexicains); Femmes artistes américaines d'origine mexicaine; Nationalisme et littérature -- États-Unis -- Histoire; LITERARY CRITICISM -- American -- General; SOCIAL SCIENCE -- Ethnic Studies -- Hispanic American Studies; American literature -- Mexican American authors; American literature -- Women authors; Identity (Psychology) in literature; Mexican American arts; Mexican American women artists; Mexican American women in literature; Mexican Americans in literature; Nationalism and literature; United States; Criticism, interpretation, etc; History